PENGEMBANGAN VIDEO PEMBELAJARAN MATERI KEMAGNETAN (UPEJ Unnes Physics Education Journal, 2017)
The limitation of space and time became the obstacle in the effort to improve the learning quality. Lecturer as the fasilitator got difficulty to present a media so that abstract material can be easily understood. The purpose of this research is to find out the characteristics and the worthiness of instructional video of magnetism. The procedure of this research suitable with the method of this Research and Development (R&D). The focus of this research is development of instructional video of magnetism in Basic Physics 2. Instrument used in this research are Worthiness Questionare in the form of Likert scale consist of Validation Questionare from media expert and material expert also Questionare of student response to the instructional video of magnetism. Validation result from material expert up to 89,58 % and 77, 08 %. While the validation result from media expert up to 78,13 % and 87,00 % and result the questionare of student response have the percentage of 85,83%, 88,73%, and 87,50%. The characteristics of instructional video of magnetism according to the aspect of media include Maintanable, Usability, Compatibility, Reusable, Good ilustration, Good Audio, Communicative and Good Visualisation. According to the aspect of material include: Suitable to the theme of magnetism, Accurate, Most Up to Date, and Good Material Output.